ANALISIS PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN - Lite Lite (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2017)
This study aims to determine: (1) the effect of product quality to customer satisfaction GSM Sim Card Prepaid XL Palangka Raya, (2) the effect of service quality on customer satisfaction GSM Sim Card Prepaid XL Palangka Raya, (3) the effect of price on consumer satisfaction GSM Sim Card Prepaid XL Palangka Raya, and (4) the effect of product quality, service quality, and price together on consumer satisfaction Prepaid Sim Card GSM XL Palangka Raya.This type of research used in this study was a survey. The population in this study are all consumers of Prepaid GSM Sim Card XL in the city of Palangka Raya. The sampling technique using purposive sampling method with a sample size of 200 people. The technique of collecting data using questionnaires that have been tested for validity and reliability. Data analysis techniques used to answer the hypothesis is multiple regression.The results showed that: (1) There is a positive effect product quality to customer satisfaction Prepaid Sim Card GSM XL Palangka Raya, evidenced from t value of 4.404 with a significance value of 0.000 <0.05; and a regression coefficient of 0.201, (2) There is a positive effect of service quality on customer satisfaction Prepaid Sim Card GSM XL Palangka Raya, evidenced from t value of 5.494 with a significance value of 0.000 <0.05 and a regression coefficient of 0.245, (3) there price positive influence on consumer satisfaction Prepaid Sim Card GSM XL Palangka Raya. It was proven that brand trust variable research results obtained t value of 5.074 with a significance value of 0.000 (0.000<0.05) and the regression coefficient has a positive value of 0.280, and (4) There is the influence of product quality, service quality, and price together on consumer satisfaction Prepaid Sim Card GSM XL Palangka Raya, evident from the calculated F value of 43.312 with a significance of 0.000<0.05.Keywords: Quality Products, Service Quality, Price, and Customer Satisfaction